Pemberian Reward and Punishment dalam Membentuk Karakter Disiplin Anak pada Sekolah Madrasah Ibtidaiyah: Giving Rewards and Punishments in Shaping Children's Disciplined Characters at Madrasah Ibtidaiyah Schools - Novitasari, Annisa (Halaqa: Islamic Education Journal, 2019)
In school learning activities the teacher has the task of educating and teaching students. As a teacher, the teacher is tasked with transferring knowledge to his students to become knowledgeable and well-behaved people. Therefore, teachers need a method of reward and punishment. With the existence of reward and punishment students will behave better and not repeat the negative deeds they have done and the children are more enthusiastic in learning to further improve their achievements.This type of research uses a qualitative descriptive method with a focus of research on the implementation of Reward and Punishment in shaping the character of Children, the subjects of this study were students of grade IV and V in MI Sunan Kalijaga Ketimang Wonoayu Sidoarjo. The technique of collecting data uses observation, interviews and documentation. The results of this study are the application of MI Sunan Kalijaga Ketimang Wonoayu provides a reward when the child performs a good action and gives punishment when the child commits an act that violates the rules orderly, in the application of its giving MI Sunan Kalijaga Ketimang Wonoayu always considered the situation and conditions so that the provision of reward and punishment was in accordance with the needs. The forms of reward given are verbal and non-verbal rewards while punishment is also the same, the teacher gives verbal punishment in the form of verbal reprimand, and non-verbal punishment in the form of recording student names in the violation book followed by mental guidance by calling parents and memorizing several letters in the Qur'an.